(3CSGSjGJ Yde GdMGShH (B:s (3WQb hJWHjbGJ HdZI HjSc (B/s - (3GHQGgje, eYf YHO GdMejOs ((3YeGf(B: s (3eDSSI GdhQGb ddfTQ hGdJhRjY(B, s, 2000)
(3ebOeI aj GdMGShH(B- (3GdCfXeI GdYOOjI(B- (3GdHhGHGJ GdefWbjI(B- (3WQb Md GdeSGFd(B- (3YHGQGJ GdEONGd hGdENQGL(B- (3Led GdJMce hGdSjWQI(B- (3GdefXheGJ(B- (3GdQhJjf GdaQYj hGdOhGds
Keywords: (3GdMGShH(B- (3Ydes; (3dZGJ GdHQeLI(B- (3dZI HjScs